2003
DOI: 10.5713/ajas.2003.1722
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cotton Stems Addition on the Chemical Composition and In Sacco Dry Matter Digestibility of Pearl Millet Silage

Abstract: Animal management and feedingThe experiment was conducted on two adult rumen fistulated buffaloes (Bubalis bubalis) averaging 350 kg body weight. During the experiment the animals were kept

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
2
2
Order By: Relevance
“…The Fiber of Bt and non-Bt CCR in bolls was not significantly different. However, this result of 53.7% in Bt and 44.2% in Non-Bt CCR in this study was in the range of 43.0-64.9% reported previously [4,[21][22][23][24][25][26]. While fiber of Bt and non-BtCCR in tender branches was significantly higher in non-BtCCR.…”
Section: Resultscontrasting
confidence: 67%
See 2 more Smart Citations
“…The Fiber of Bt and non-Bt CCR in bolls was not significantly different. However, this result of 53.7% in Bt and 44.2% in Non-Bt CCR in this study was in the range of 43.0-64.9% reported previously [4,[21][22][23][24][25][26]. While fiber of Bt and non-BtCCR in tender branches was significantly higher in non-BtCCR.…”
Section: Resultscontrasting
confidence: 67%
“…The protein was higher in BtCCR compared to non-Bt CCR in both bolls and tender branches. However, the CP of bolls and tender branches in this result of 11.2 and 7.3 in Bt and 6.6 and 6.1% in non-Bt CCR respectively, only CP of bolls in BtCCR was out of the range of 3.5-9.6% reported previously [4,[21][22][23][24][25][26]. The Fiber of Bt and non-Bt CCR in bolls was not significantly different.…”
Section: Resultscontrasting
confidence: 52%
See 1 more Smart Citation
“…Azim et al (2000) reported that in situ DM digestibility of maize silage was 55.70%. The in situ DM digestibility of millet silage incubated in the rumen for 48 h was 64.39% (Grewal et al 2003).…”
Section: Introductionmentioning
confidence: 99%